Supporting international students with discipline-specific, course-embedded ALL instruction - Wilson, Owen; Chan, Billy (Journal of Academic Language and Learning, 2025)
Academic language and learning (ALL) support at Australian universities plays a crucial role in the academic success, acculturation and wellbeing of many student cohorts, including international students. This paper examines the implementation and effectiveness of a course-embedded, discipline-specific ALL support initiative, SCANA (Student Communication and Needs Analysis), at the University of Sydney. The paper evaluates the iterative development of SCANA support within a single postgraduate education program over four semesters, and focuses on how and why the design and delivery of ALL instruction changed over this time, towards an increased focus on digital literacy and a more inclusive learning environment. It complements this evaluation with student performance data and student feedback data demonstrating improvements in academic outcomes and student satisfaction. Ultimately, this paper highlights the importance of discipline-specific, course-embedded ALL support in addressing the challenges faced by international students at Australian universities and offers a practitioner’s view of the iterative development of one particular ALL support initiative. This research contributes to the growing body of literature on best practices in ALL support, particularly the inclusion of digital and AI resources and a focus on digital literacy.